Research on the Energy-Saving Design Path of Rural Farmhouses under the Background of Ecological Livability - Jingyuan Shi; Qiuna Li (Advances in Materials Science and Engineering)
Different from the state of large-scale energy use and concentrated energy conservation in urban areas, the state of energy use and energy conservation in rural areas has its own characteristics and typical problems. Rural areas have been concentrated on the multiple differences in economic, social, and construction characteristics such as mountain and peace dam topography, natural and artificial construction, developed and underdeveloped, rapid urban development, and relatively backward rural development. It has practical problems that need to be solved urgently, such as the “insufficient savings” in the construction of farmhouses and the “insufficient open source” of clean energy applications. The discussion will be conducted from three aspects: the planning and layout design of rural houses in Chongqing, the performance of the enclosure structure of rural houses in key seasons, and the application of renewable clean energy in rural houses. Then put forward is the energy-saving design path of Chongqing farmhouse. It aims to improve the indoor and outdoor thermal environment of farmhouses, saving heating energy consumption in winter and air-conditioning energy consumption in summer and effectively benefit users to use renewable energy such as biogas, straw, and solar energy. Finally, explore the adaptability between the design methods of farmhouses and the local characteristics of Chongqing’s rural areas. In the work of Chongqing Design Going to the Countryside, we create a contemporary farmhouse case that is not only energy-saving but also has good indoor and outdoor space quality. It also provides a reference for the energy-saving design of farmhouses in Chongqing and other regions in China.